Reduced Coulomb interaction in organic solar cells by the introduction of inorganic high‐k nanostructured materials. Issue 9 (24th April 2013) - Engel, Miriam; Schaefer, David; Erni, Daniel; Benson, Niels; Schmechel, Roland
<x xml:space="preserve">Abstract</x> In this paper a concept is introduced, which allows for reduced Coulomb interaction in organic solar cells and as such for enhanced power conversion efficiencies. The concept is based on the introduction of electrically insulating, nanostructured high‐k materials into the organic matrix, which do not contribute to the charge transport; however, enhance the effective permittivity of the organic active layer and thereby reduce the Coulomb interaction. Using an analytical model, it is demonstrated that even at a distance of 20 nm to the organic/inorganic interface of the nanostructure, the Coulomb interaction in the organic semiconductor can be reduced by more than 15%. The concept is implemented using P3HT:PCBM solar cells with integrated high‐k nanoparticles (strontium titanate). It could be demonstrated that in comparison to a reference cell without integrated nanoparticles, the power conversion efficiencies is improved by ∼17%.